Musculoskeletal Physiotherapy in the Emergency Department – Evaluation of a New Physiotherapy Service in a Swiss University Hospital - Winteler, Balz; Geese, Franziska; Lehmann, Beat; Schmitt, Kai-Uwe (physioscience, 2021)
Background Many countries report a significant increase in emergency department (ED) visits. Patients with musculoskeletal disorders account for a large proportion of non-urgent cases.Objective Characterization and evaluation of a new service that provides immediate access to physiotherapy for patients in the ED.Method To characterize a new service at the Department of Emergency Medicine, Bern University Hospital, and to evaluate first experiences with it, a mixed methods approach was chosen. Data was collected from the electronic patient file and from a logbook kept by the physiotherapists. In addition, guideline-based interviews with involved health care staff were conducted.Results During the 63 days of the pilot study 79 patients were treated by physiotherapists. The most frequently reported patient complaint was back pain (47 %). Interventions included taking the medical history, performing manual tests and multimodal treatment and developing recommendations for further treatment. In 59 % of patients no medical imaging and in 58 % no additional physiotherapy was prescribed. Patients rated the physiotherapeutic service as very good or excellent (88 %). Physiotherapy was experienced as positive and appreciated by the other professions, and all interviewees emphasized the added value for patients.Conclusion The pilot study indicates that the physiotherapeutic consultation service has the potential to improve quality of care. The findings of this study are therefore valuable when considering the introduction of such a service in an ED.
Keywords: musculoskeletal diseases; emergency service; hospital; specialty physical therapy